2022
DOI: 10.3389/fimmu.2022.956982
|View full text |Cite|
|
Sign up to set email alerts
|

The efficacy and safety analysis of first-line immune checkpoint inhibitors in pulmonary sarcomatoid carcinoma

Abstract: BackgroundPulmonary sarcomatoid carcinoma (PSC) is a rare and aggressive disease without standardized treatment strategies. The efficacy of second-line or beyond immune checkpoint inhibitors (ICIs) has been proven in recent studies, whereas the evidence for first-line immunotherapy for PSC is still limited to case reports and remains poorly understood.Materials and methodsThis was a multicenter, retrospective analysis of 21 patients with a histological diagnosis of PSC who received ICI as first-line therapy fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Besides, no serious TRAEs (grade ⩾3) were noticed. 15 Matsumoto et al 16 reported a case with advanced PSC who received pembrolizumab monotherapy as first-line treatment and achieved a partial response (PR) after three treatment cycles with an acceptable safety profile.…”
Section: Immunotherapy For Pscmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, no serious TRAEs (grade ⩾3) were noticed. 15 Matsumoto et al 16 reported a case with advanced PSC who received pembrolizumab monotherapy as first-line treatment and achieved a partial response (PR) after three treatment cycles with an acceptable safety profile.…”
Section: Immunotherapy For Pscmentioning
confidence: 99%
“…Importantly, both regimens were generally well tolerated. 15 Furthermore, Li et al 20 reported a case of advanced PSC switched to tislelizumab plus anlotinib therapy after failure of first-line conventional chemotherapy, and after 13 cycles of the combined treatment, the patient achieved complete response (CR) and was still on the drug.…”
Section: Immunotherapy For Pscmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the impact of first-line immunotherapy on patients with PSC, a multicenter retrospective study enrolled 21 patients with PSC receiving first-line immunotherapy ( 161 ). Of these patients, 14 received immunotherapy combined with anlotinib (tislelizumab: 7; camrelizumab: 4; sintilimab: 2; pembrolizumab: 1), 4 received immunotherapy combined with platinum-based chemotherapy (pembrolizumab: 2; sintilimab: 1; durvalumab: 1), and 3 patients received immune monotherapy (camrelizumab: 2; sintilimab: 1) ( 161 ). The ORR was 57.1%, the disease control rate (DCR) was 81% (PR: 12; SD: 5; PD: 4), the median PFS was 9.2 months, and the median OS was 22.8 months ( 161 ).…”
Section: Clinical Characteristics and Treatmentmentioning
confidence: 99%
“…26 Neutrophil extracellular traps (NETs) are network structures released from activated neutrophils. NETs promote tumor metastasis by inducing epithelial-mesenchymal transition in non-small-cell lung cancer, 68 gastric cancer, 69 and CRC. 70 In addition, NETs shield tumor cells from clearance by immune cells, resulting in increased tumor growth.…”
Section: Biglycan Is a Novel Therapeutic Target For Cancer Therapymentioning
confidence: 99%